Removal methods for invasive species Amorpha fruticosa - example of Odransko polje - Lončar, Goran, ekolog; Hršak, Vladimir; Kerovec, Maja; Dekanić, Stjepan; Vranješ, Domagoj (2020)
Amorpha fruticosa is an invasive plant species that occurs in wide range of habitat types, including lowland floodplains. It grows very dense and changes the composition of communities by suppressing indigenous species, resulting in significantly reduced variety of flora in the area. In Odransko polje Amorpha fruticosa is widely spread. One of the tasks of Appropriate assessment of project "Flood protection system of Sisak area" was to determine the locations where material for embankment construction should be taken. The locations should be acceptable both from the aspect of nature protection and from the economic point of view (proximity to embankment due to lowering material transport costs, locations which are not private property, etc.). The locations where A. fruticosa is dominant plant were suggested for excavation. This paper will give overview of removal and disposal methods for this invasive species, which reduce the possibility of its spreading and re-appearing. Also, positive impacts of using proposed locations for material excavation will be shown – decrease in A. fruticosa abundance, increase of habitat diversity, increase in the presence of target habitats and target species habitats etc. Additionally, good practices for selection of excavation sites will be given, including guidelines for their sanation and landscape design.
Bibliografija: str. 83.
Summary.
Keywords: Amorpha fruticosa -- Invazivne vrste -- Poplavna područja; Odransko polje